Clinical recommendations for telehealth and electronic consultations in the veterans health administration referral coordination initiative - David E. Winchester; Lisa Arfons (American Heart Journal Plus)
MeSH Keywords: TelemedicineVeterans health servicesCardiologyReferralConsultation